The STUDI INTERAKSI OBAT ANTIHIPERLIPIDEMIA PADA PASIEN RAWAT JALAN DI SALAH SATU RUMAH SAKIT SWASTA CIKAMPEK - Amal, Andi Nurzakiah; Agustini, Dewi Darwati; Amal, Surya (Jurnal Buana Farma, 2024)
Hyperlipidemia is a lipid metabolism disorder characterized by an increase in total cholesterol levels in the blood, which is a risk factor for various cardiovascular diseases. Treatment of hyperlipidemia is often combined with other drugs, increasing the potential for drug interactions. This study aims to identify the severity of antihyperlipidemia drug interactions in outpatients in private hospitals in Cikampek during the period of June to December 2023. The research uses an analytical survey design with a retrospective approach. Data were obtained from 251 patient prescriptions that met the inclusion criteria and were analyzed univariably using the Stockley Drug Interaction and drugs.com application. The results showed that 67.65% of prescriptions had potential drug interactions, while 32.35% did not. Patients aged 50–59 years were the largest group (42.6%) receiving antihyperlipidemia, with simvastatin being the most frequently prescribed drug and causing drug interactions most often (51.11%). Of the 135 cases of drug interactions identified, moderate severity accounted for 57.03%, while major severity reached 46.97%. No cases with minor severity were found. This study highlights the importance of monitoring drug interactions to prevent more serious risks in hyperlipidemia patients.